IMPLEMENTASI ALGORITMA FAST FOURIER TRANSFORM (FFT) DAN ALGORITMA HARMONIC PRODUCT SPECTRUM (HPS) Pada TUNER GITAR BERBASIS ANDROID - Firdaus Noor Abdillah (NUANSA INFORMATIKA, 2017)
Music is something that everyone is interested in, but not everyone can play a musical instrument, especially a guitar. Many people who love this instrument but many also have not understood about guitar tuning in case of fals there is a guitar string. How to tuning the guitar will be difficult for a beginner who has not understood about guitar tuning poses. The easiest solution is to use an electronic guitar tuner, but the tool is quite expensive and less flexible to carry anywhere. In this thesis, the author designed an android-based guitar tuner application to solve the problem. Guitar tuner application that will be made using Fast Fourier Transform algorithm that serves to calculate Fourier Discrit's transformation quickly and efficiently, and using Harmonic Product Spectrum algorithm to perform frequency harmonization process to know the basic tone frequency of guitar strings and process the frequency so as to produce output in the form of needle indicator parameters in the form of interface. From the results of this study obtained results in the form of guitar tuner application that is able to function well to help the process of guitar tuning.Keyword           : Aplikasi, Android, Tuner Gitar, FFT(Fast Fourier Transform), HPS(Harmonic Product Spectrum), Frekuensi